Melioidosis in a returning traveller. (18th April 2013) - Ismail, Alaa; Buckley, Adam; Dubrey, Simon William
Abstract : A 66-year-old man returned to the UK from Thailand with a 2-week history of new confusion, hallucinations, fever with rigours and productive cough. He had not responded to (unspecified) antibiotic treatment in Thailand. On examination he was afebrile, with an abbreviated mental test score of 8/10 and no other findings on systemic examination. He was treated with ceftriaxone in response to discovery of a Gram-negative organism in blood. This was converted to meropenem on the clinical suspicion of our microbiologist, on the basis of a history of contact with surface water in the Far East. A blood culture subsequently confirmed Burkholderia pseudomallei . His condition remained stable for approximately 4 days, but then deteriorated over the course of the next 2 weeks with pneumonia and subsequent formation of disseminated abscesses. Treatment was withdrawn as his condition deteriorated to the point at which survival was deemed impossible and he subsequently died.